The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11897-014-0250-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered Breathing Syndrome in Heart Failure: Newer Insights and Treatment Options

Abstract: In patients with heart failure (HF), altered breathing patterns, including periodic breathing, Cheyne-Stokes breathing, and oscillatory ventilation, are seen in several situations. Since all forms of altered breathing cause similar detrimental effects on clinical outcomes, they may be considered collectively as an "altered breathing syndrome." Altered breathing syndrome should be recognized as a comorbid condition of HF and as a potential therapeutic target. In this review, we discuss mechanisms and therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Physiologic PB is not seen in healthy children or adults except with exposure to acute hypoxia on ascending to high altitude. ( 19 ) Pathologic forms of PB occur in adults with acute or chronic illness, including Cheyne-Stokes respiration in congestive heart failure,( 20 ) and central PB following brain injury such as stroke. ( 21 ) These forms of PB are linked to poor outcomes and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologic PB is not seen in healthy children or adults except with exposure to acute hypoxia on ascending to high altitude. ( 19 ) Pathologic forms of PB occur in adults with acute or chronic illness, including Cheyne-Stokes respiration in congestive heart failure,( 20 ) and central PB following brain injury such as stroke. ( 21 ) These forms of PB are linked to poor outcomes and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This may be associated with the stabilization of respiration by ASV, which has sympathoinhibitory effects (Ushijima et al, 2014 ). In a study by Ushijima et al ( 2014 ), the sympathoinhibitory effects by ASV were predominantly observed in patients with periodic breathing while awake, which is generally observed in patients with advanced HF (Tomita et al, 2015 ). Despite the lack of assessment of such periodic breathing while awake, the findings of Ushijima's study and our findings that patients with a low baseline fSVI who are also likely to have periodic breathing while awake showed significant reductions in the SVR index in addition to the fact that all of our patients have SDB, which frequently coexists with periodic breathing while awake (Emdin et al, 2017 ), may help explain why ASV showed similar alleviation of MR and changes in fSVI to CPAP at 8 cm H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Since all forms of these abnormal breathing patterns cause similar detrimental effects on clinical outcomes, they are considered collectively as "altered breathing syndrome," which should be recognized as a comorbid condition of heart failure. 16) The mechanisms of altered breathing syndrome include but are not limited to prolongation of circulation time accompanied by severe heart failure, excessive activated reflex of the chemoreceptor/baroreceptor, and increased dead space due to pleural effusion and pulmonary edema. 17) In chronic heart failure patients with central sleep apnea and Cheyne-Stokes breathing, hypoxemia may contribute to increased C-reactive protein levels and augment the release of inflammatory cytokines, adhesion molecules, and insulin.…”
mentioning
confidence: 99%